Sie sind auf Seite 1von 2

Tangent plane

Nika kurdadze
June 8, 2020

Exercise 2
We have to find the tangent plane of the curve x2 + y 2 + 4z 2 = 16 at the point
(a, b, c). I will show two different ways of solving this problem.

method 1
lets make z the function of x and y. we will have:
1p
z(x, y) = 16 − x2 − y 2
2
−x
z1 (x, y) = p
2 16 − x2 − y 2
−y
z2 (x, y) = p
2 16 − x2 − y 2
so, normal vector will be:
−a −b
√ i+ √ j−k
2
2 16 − a − b2 2 16 − a2 − b2
so, the equation of tangent plane is:
−a −b
√ (x − a) + √ (y − b) − (z − c) = 0
2
2 16 − a − b2 2 16 − a2 − b2
which simplifies to:
p
a(x − a) + b(x − b) + 2 16 − a2 − b2 (z − c) = 0

method 2
The second method is more easy and simply generalizes in higher dimensions.
let us consider the simpler task. assume that we have to find the tangent line
of f (x, y) = 0 at point (a,b). since, f(x,y) is constant through the curve, its
increase and decrease through x and y directions must add up to zero at any

1
point on this curve. since line is good approximation of the curve near the point,
we will have:
f1 (a, b)(x − a) + f2 (a, b)(y − b) = 0
If we have function of 3 variables, we would have tangent plane, but still sum
of all increases and decreases near the point must be zero, because function is
constant. so for 3 variable function, at point (a,b,c) we would have tangent
plane, that has equation:

f1 (a, b, c)(x − a) + f2 (a, b, c)(y − b) + f3 (a, b, c)(z − c) = 0 (1)

It is clear how we can generalize it in n dimension. if we have function of n


variables f (x1 , x2 ...xn ) = 0 its tangent plane at the point (a1 , a2 ...an ) will have
the equation:

f1 (a1 , a2 ...an )(x1 −a1 )+f2 (a1 , a2 ...an )(x2 −a2 )+...+fn (a1 , a2 ...an )(xn −an ) = 0
(2)
Now, lets solve our problem. we have f (x, y, z) = 16, where
f (x, y, z) = x2 + y 2 + 4z 2

f1 (x, y, z) = 2x
f2 (x, y, z) = 2y
f3 (x, y, z) = 8z
so, the tangent plane will have the equation
2a(x − a) + 2b(y − b) + 8c(z − c) = 0 ⇒ a(x − a) + b(x − b) + 4c(z − c) = 0
(3)
It may look different from the answer√ that we get from method 1, but if we
substitute the value of c, that is 21 16 − a2 − b2 , we will get, that tangent plane
has equation:
p
a(x − a) + b(x − b) + 2 16 − a2 − b2 (z − c) = 0

which is same as we got from method 1.